GIS integrating local environmental knowledge in disaster preparedness community based landslide hazard mapping in Baguio City, Philippines - Winastu, Hendra
Landslides are one of the natural disasters that have a big effect on human lives, from the loss in the activities, investments, to the loss of life itself. Baguio City is known as the Summer Capital of the Philippines and is a landslide prone area because of its geologic and geographic setting. Provision of good information is needed as basis for a landslide risk management system to make the local people aware and lessen the adverse effects of natural occurrences in the future.